Tingkat Penerimaan Panelis terhadap Beras Rawa Lebak di Sumatera Selatan - Merynda Indriyani Syafutri; Filli Pratama; Friska Syaiful; Achmad Faizal; Riki Anggara (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2019)
Syafutri MI, Pratama F, Syaiful F, Faizal A, Anggara R. 2019. Tingkat penerimaan panelis terhadap beras rawa lebak di Sumatera Selatan. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 522-527. Palembang: Unsri Press. One of crops planted in swamp area in South Sumatra Province is rice. Rice produced from rice plant of swamp area had certain characteristics, including sensory characteristics. The objective of this research was to learn the level of panelist preference of rice produced from swamp area in South Sumatra. The varieties of swamp rice sample were IR 42, IR 10, IR 64, Mekongga, Ciherang, Ciherang Dempo, Ciliwung, Ciliwung Jumbo, and Rojo Lele. Swamp rice samples were obtained from 4 districts, namely Ogan Ilir, Ogan Komering Ilir, Banyuasin, and Ogan Komering Ulu Timur. The level of panelists preference was measured using a hedonic test for milled rice and cooked rice. The hedonic scores used were 1 (very dislike), 2 (dislike), 3 (common), 4 (like), and 5 (very like). The parameters observed were aroma and color for milled rice, and aroma, color, texture and taste for cooked rice. The results showed that panelists gave a rating of